2014
DOI: 10.5005/jp-journals-10024-1512
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Teeth Submitted to Several Internal Bleaching Protocols

Abstract: Aim The aim of this study was to evaluate the fracture resistance of teeth submitted to several internal bleaching protocols using 35% hydrogen peroxide (35HP), 37% carbamide peroxide (37CP), 15% hydrogen peroxide with titanium dioxide nanoparticles (15HPTiO2) photoactivated by LED-laser or sodium perborate (SP). Materials and methods After endodontic treatment, fifty bovine extracted teeth were divided into five groups (n = 10): G1—unbleached; G2—35HP; G3—37CP; G4—15HPTiO2 photoactivated by LED-laser and G5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Walking bleach procedure cause more reduction in fracture resistance of teeth due to the residues of bleaching agents that remains within the dentinal tubules, and continuous mechanical and thermal alterations that can occur intra-orally. Our study results are in line with those of Leonardo Rde et al [ 18 ]. They evaluated the fracture resistance of teeth subjected to several internal bleaching protocols using 35% hydrogen peroxide, 37% carbamide peroxide, and 15% hydrogen peroxide with titanium dioxide nanoparticles photoactivated by LED-laser or sodium perborate.…”
Section: Discussionsupporting
confidence: 94%
“…Walking bleach procedure cause more reduction in fracture resistance of teeth due to the residues of bleaching agents that remains within the dentinal tubules, and continuous mechanical and thermal alterations that can occur intra-orally. Our study results are in line with those of Leonardo Rde et al [ 18 ]. They evaluated the fracture resistance of teeth subjected to several internal bleaching protocols using 35% hydrogen peroxide, 37% carbamide peroxide, and 15% hydrogen peroxide with titanium dioxide nanoparticles photoactivated by LED-laser or sodium perborate.…”
Section: Discussionsupporting
confidence: 94%
“…30,31 In the fracture resistance assessment, a force was applied with an angle of incidence of 135° relative to the long axis of the root to simulate natural conditions. 2,11 Praddep et al 32 have observed that the fracture resistance of teeth bleached with peroxides is similar to that of sound teeth when an axial force is applied. However, this angle of incidence is not consistent with clinical conditions for upper incisors.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, the gel was aspirated; the dental crown was then copiously rinsed with a gentle spray of water for 1 min, dried and immediately restored in a manner similar to the treatment used for G2. 2 For G4 (HP + SA + CR), after a bleaching protocol similar to that used for G3 was used, 10% sodium ascorbate gel (Apothicário, Araçatuba, Brazil) was applied to the buccal surface for 15 min and within the pulp chamber for 10 minutes. Subsequently, the tooth was rinsed with a gentle spray of water for 15 s and then immediately restored with a procedure similar to that used for G2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The penetration is significantly higher with sodium perborate-hydrogen peroxide mixtures than with mixtures of sodium perborate tetrahydrate and water. Several studies have demonstrated that sodium perborate with water is an effective and safe bleaching agent [13, 1719]. …”
Section: Discussionmentioning
confidence: 99%